Legal Issues Concerning Delivery and Redelivery of the Vessel in Time Charterparties - Ceren Cerit (2019)
This research analyses time charters, in particular the law regarding the delivery and redelivery of the chartered vessel. These two key stages in the context of a time charterparty agreement have been chosen since legal and practical problems often arise and the law in this area is constantly developed through the judgments of courts. The author has identified six areas which are particularly significant and need close evaluation. These are the construction of the methods used by the parties to define the charter period and ascertaining the duration of the charter; the matters relating to timely delivery of the vessel; the extent of the shipowner’s right to keep the charter alive upon early redelivery of the vessel by the charterer; problems raised by the issue of how the assessment of damages is made in case of early redelivery of the vessel (underlap); the impact of the charterer’s last voyage order on occurrence of late redelivery of the vessel; and lastly the issue of how the assessment of damages is made in case of late redelivery of the vessel (overlap). This research not only identifies the legal position by mapping shipowner’s and charterer’s rights and liabilities relating to the areas identified above but it also evaluates the accuracy of the settled law in this regard, highlights the gaps and indicates areas that should be reformed through contractual mechanisms. The analysis in this thesis is based on English law.